Pengembangan Comic Book Materi Sumber Daya Alam Kelas IV SD Islam Terpadu Raudhaturrahmah Pekanbaru - Tia Dita Putri Latifa Yuwono; Muhammad Ilham Syarif; Susilawati - Susilawati (el-Ibtidaiy:Journal of Primary Education, 2022)
This study aims to describe the design and validity of natural resource comic books and to describe the responses of educators and students to natural resource comic books. The use of teaching materials in schools that are less varied and the availability of teaching materials that are textbook in nature with students who are less interested in reading textbooks are the basis for conducting research. This research is a Research and Development research using the Borg and Gall development model. To see the validity of the comics, validation was carried out by 2 design experts and 2 material experts using a validation sheet, while to see the responses of comic users, a trial was conducted on 6 educators and 15 students in grade IV SDIT Raudhaturrahmah Pekanbaru using a questionnaire. The data obtained were analyzed using qualitative descriptive analysis techniques and quantitative descriptive analysis. Validation by design experts obtained a score of 94% in the "Very Good" category and material experts obtained a score of 90% in the "Very Good" category. In the comics trial phase, it got a score of 90.7% in the "Very Good" category for the educator response product trial and a score of 98.5% in the "Very Good" category for the student response product trial. The results of this studyis a valid comic to be used as teaching material